The Effect of an Augmented Reality-Based Discovery Learning Model on Students' Language Proficiency: A Meta-Analysis - Pateda, Lamsike; Saleh, Yuwin Rustam; Pido, Nur Wahidah Thayib; Adam, Sumarlin; Wantu, Hasyim Mahmud (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to determine the influence of augmented reality-based discovery learning models on students' language skills. This type of research is quantitative research with a meta-analysis approach. The eligibility criteria are that the research is published from 2021-2024, SINTA or Scopus must index the research, the research must be an experimental method or quasi-experiment, the research must be open access, and the research data must be complete to calculate the effect size value. Tracing data sources include Google Scholar, ERIC, Taylor of Francis, IEEE and Scopus. The data collection technique is observation through databases. The data in this study was filtered using the PRISMA 2020 method. Data analysis in the study by calculating the effect size value of each survey with the JSAP 0.8.5 application. The analysis of 22 studies concluded that the augmented reality-based discovery learning model significantly influenced students' language skills with a value of d = 1,029 in the high effect size category. This finding positively influences teachers to apply this model to encourage students' language skills in Indonesian learning.Â Â